Online school report card / Noor Azimah Hassan - Hassan, Noor Azimah (2003)
Online school report card is being developed to help teachers keeping the current record of student's examination result and disseminate it to parents and guardians. It is an introduction of a new communication medium via Internet between parents or guardians and school administrator. It will help them to view students' performance easier as it is delivered in an efficient way. They will not have to rely to the students to bring back the report card as it can be accessed anywhere and anytime. Only authorized user (teachers) can update the web database while other parties can only view the record.